Technological Learning and Capability-Building: How do African Telecommunication Firms Learn? - Marcelle, Gillian (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2003)
This paper presents the results of a larger study that focusses on technological learning in developing country firms, using empirical data from 26 telecommunication firms in Uganda, Ghana, Tanzania and South Africa. The paper adds to knowledge by providing a cross-disciplinary study of how African firms undertake technological learning and capability-building. The conceptual framework used in the paper, the TCB system approach, suggests that the underdevelopment of the strategic and systematic management of technological learning capability development is a major constraint for developing country firms and cannot be explained by country-level factors only. It therefore suggests that a simultaneous focus on internal factors that contribute to effectiveness, and on boundary conditions, is necessary. This paper focuses on the internal, intrafirm dimension and provides insights on how features such as ability to manage cultural change, leadership and organisational integration influence and explain variation in the ability of telecom firms to build capabilities. These insights have implications for firm strategy and policy and offer avenues for future research.